Dataset for 10.1016/j.fct.2020.111554 - Muñoz, Israel; Guàrdia, Maria Dolors; Arnau, Jacint; Dalgaard, Paw; Bover, Sara; Fernandes, José O.; Monteiro, Carolina; Cunha, Sara C.; Gonçalves, Amparo; Nunes, Maria Leonor; Oliveira, Helena (Zenodo, 2020)
Dataset corresponding to the following article: Israel Muñoz, Maria Dolors Guàrdia, Jacint Arnau, Paw Dalgaard, Sara Bover, José O. Fernandes, Carolina Monteiro, Sara C. Cunha, Amparo Gonçalves, Maria Leonor Nunes, Helena Oliveira. (2020).Effect of the sodium reduction and smoking system on quality and safety of smoked salmon (Salmo salar),Food and Chemical Toxicology, 139, 111554.